AN ANALYSIS OF STUDENT’S CRITICAL THINKING SKILLS IN PHYSICS LESSON IN SMA 8 PEKANBARU - Afrima Nori; Zulirfan Zulirfan; Zuhdi Ma’aruf (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2019)
Critical thinking ability is one of the high-level thinking skills that are problem solving skills essentially. The main purpose of this research is to describe the level of students' critical thinking skills in physics subjects at SMAN 8 Pekanbaru. The population in the study were 316 students of grade 11 of SMAN 8 Pekanbaru. Samples were taken by purposive sampling so that a sample of 33 students. The instrument of this research is a test of critical thinking skills which is based on 12 indicators of critical thinking skills. Data was collected by giving a test of critical thinking skills to the sample. Data analysis in this study used descriptive, which provide an overview of the level of critical thinking skills. The results of this study provide information that the average percentage of critical thinking skills students of SMAN 8 Pekanbaru is 50.88% with a moderate level of critical thinking ability.